The Long-Term Effects of Poland’s Accession to the European Union: A Literature Review - Jan Jakub Michałek; Jan Hagemejer (Studia Europejskie, 2024)
The year 2024 marks 20 years since Poland joined the European Union. In this paper, the authors review the economic literature analysing the long-term economic effects of Poland’s membership in the EU. Their study is based on international and Polish literature referring mainly to partial and general equilibrium analyses. They show both the sectoral effects, as related to different EU policies, as well as the overall consequences of membership for the level of welfare of Polish society. The authors ﬁrst discuss the trade effects in the context of the removal of barriers to the movement of goods within the Single European Market. Next, the consequences of the inﬂow of funds from the EU budget which ﬁnance the country’s structural funds and the Common Agricultural Policy, which are of particular importance to the Polish economy are discussed. A review of the consequences of the inﬂow of foreign direct investment from EU countries to Poland and the effects of labour migration within the EU is then conducted. A review of the related welfare consequences by aggregating the effects of individual policies and making an overall assessment based on a synthetic control method is then summarised. The authors then refer to their estimations showing that, thanks to EU accession, Poland’s GDP per capita 15 years after accession was higher by almost 55% compared to the counterfactual scenario of non-accession.